2020
DOI: 10.1200/jco.2020.38.15_suppl.3081
|View full text |Cite
|
Sign up to set email alerts
|

Targeting HER2 in combination with anti-PD-1 and chemotherapy confers a significant tumor shrinkage of gastric cancer: A multi-institutional phase Ib/II trial of first-line triplet regimen (pembrolizumab, trastuzumab, chemotherapy) for HER2-positive advanced gastric cancer (AGC).

Abstract: 3081 Background: Combining anti-PD-1 agent and trastuzumab has shown synergy in HER2 positive preclinical cancer models. We first report the result of a multi-institutional phase Ib/II trial of triple combination (pembrolizumab, trastuzumab, and chempotherapy) as first line therapy for HER2 positive AGC. (PANTHERA trial; NCT02901301). Methods: Pembrolizumab 200mg IV D1, Trastuzumab 6mg/kg (after 8mg/kg load) D1, Capecitabine 1000mg/m2 bid D1-14, and Cisplatin 80mg/m2 D1 every 3 weeks was selected as recommend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 0 publications
0
41
0
Order By: Relevance
“…Checkpoint inhibitor therapy was administered in combination with trastuzumab and chemotherapy in four studies. [14][15][16][17]24 Three of these studies investigated pembrolizumab (including the phase III KEYNOTE-811 14 and the phase I/II PANTHERA 16,17 ), and one tested avelumab. 24 Overall, median follow-up across all studies ranged from 10 to 34 months (Table 2).…”
Section: Features Of the Studies Analyzedmentioning
confidence: 99%
See 2 more Smart Citations
“…Checkpoint inhibitor therapy was administered in combination with trastuzumab and chemotherapy in four studies. [14][15][16][17]24 Three of these studies investigated pembrolizumab (including the phase III KEYNOTE-811 14 and the phase I/II PANTHERA 16,17 ), and one tested avelumab. 24 Overall, median follow-up across all studies ranged from 10 to 34 months (Table 2).…”
Section: Features Of the Studies Analyzedmentioning
confidence: 99%
“…The treatment-related AEs of all grades occurring in !30% of patients in at least two studies were nausea (33%-84%), anemia (33%-81%), and diarrhea (30%-73%; Table 3). 15,17 Grade !3 treatmentrelated AEs occurring in !10% of patients in at least two studies were neutropenia (28%-42%), anemia (11%-16%), and thrombocytopenia (7%-11%; Table 3). 15,17,24 Analysis of a select type of TEAEs across the four studies [14][15][16][17]24 of regimens containing checkpoint inhibitors, trastuzumab, and chemotherapy reveals the following ranges (Table 4): fatigue (all grades: 24%-86%; grade !3: 0%-4%); nausea (all grades: 49%-84%; grade !3: 0%-5%); diarrhea (all grades: 53%-73%; grade !3: 2%-7%); neutropenia (all grades: 19%-47%; grade !3: 0%-42%); anemia (all grades: 33%-81%; grade !3: 9%-16%); peripheral neuropathy (all grades: 19%-97%; grade !3: 0%-3%); pneumonitis (all grades: 5%; grade !3: 1%); stomatitis (all grades: 23%-38%; grade !3: 2%-5%); and PPE/HFS (all grades: 22%-23%; grade !3: 0%).…”
Section: Overall Safety Profile Of Checkpoint Inhibitors Plus Trastuzumab Plus Fluoropyrimidine Plus Platinmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from one of these trials (NCT02954536) showed that a combination of pembrolizumab, trastuzumab and chemotherapy (oxaliplatin or cisplatin) had a manageable safety profile and promising efficacy, with an ORR of 91% (95% CI: 78-97; 32 of 35 patients; six CRs) in patients with esophagogastric adenocarcinoma [30]. In another trial (NCT02901301), the ORR was 77% with pembrolizumab, trastuzumab, capecitabine and cisplatin as first-line therapy for HER-positive advanced gastric cancer [31]; the dosing schedule and patient population are similar to those of the KEYNOTE-811 trial.…”
Section: Background and Rationalementioning
confidence: 99%
“…Their success likely stems from a hot tumor microenvironment (TME) marked by MSI-H-, TMB-H- and PD-L1-positive tumors and pathological associations with Helicobacter pylori and EBV infections. In addition to chemotherapy, combining ICIs with targeted therapies such as inhibitors against the VEGF or HER-2 pathway that are capable of modulating the TME have produced encouraging results [ 92 , 93 ]. Sequential therapy from ICIs to chemotherapy is another promising strategy [ 94 ].…”
Section: Gastric and Gastroesophageal Adenocarcinomamentioning
confidence: 99%